Public Service Innovation Based on Mini Website at The United Nation and Political Agency of Probolinggo City - Ahmad Isnaini Haryanto; M Mas'ud Said; Slamet Muchsin (Universitas Muhammadiyah Gorontalo, 2021)
The innovation raised by Bakesbangpol in providing services to the public, especially the management of mass organizations is by launching the A_ormasapplication, where this application contains a database of mass organizations, registration, and reporting of mass organizations. Therefore, this study aims to analyze the implementation of public service innovations in the implementation of this application, the supporting and inhibiting factors, as well as strategies to face obstacles in the implementation of the A_ormasapplication. This study uses a qualitative approach with a descriptive type of research. Collecting data using interviews, surveys, observation, and document techniques. While the data analysis used interactive model analysis. The results of the study indicate that public service innovation in the mini web-based A_ormas Application has been running effectively, the supporting factors in this innovation are the support from the leadership, competent service personnel, adequate service facilities and infrastructure as well as central and local government assistance. While the inhibiting factors include limited personnel who master information technology, still using open-source networks, no public dialogue menu, and no reward and punishment system. Improvement efforts have also been made, including: Urging the local government to immediately realize the use of fiber optic networks so that they can improve services, submitting IT personnel to the Probolinggo City Government through the section that handles staffing and optimizing the function of the public dialogue menu.